(2.5b-9)+6b=-7

Simple and best practice solution for (2.5b-9)+6b=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2.5b-9)+6b=-7 equation:


Simplifying
(2.5b + -9) + 6b = -7

Reorder the terms:
(-9 + 2.5b) + 6b = -7

Remove parenthesis around (-9 + 2.5b)
-9 + 2.5b + 6b = -7

Combine like terms: 2.5b + 6b = 8.5b
-9 + 8.5b = -7

Solving
-9 + 8.5b = -7

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 8.5b = -7 + 9

Combine like terms: -9 + 9 = 0
0 + 8.5b = -7 + 9
8.5b = -7 + 9

Combine like terms: -7 + 9 = 2
8.5b = 2

Divide each side by '8.5'.
b = 0.2352941176

Simplifying
b = 0.2352941176

See similar equations:

| 8m-6=2 | | 5(a-1)=5 | | 5(3x+-2)=4+-6x | | 4(3x+-2)=4+-6x | | -11=7+b | | 4w+10=90 | | 43v-6=8+23v | | 12x+6=5y+10 | | 4w+10= | | 2x-3(3-7)+3= | | 3(3x+-2)=4+-6x | | Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m | | 6m-2=m+3 | | (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 | | X^2=11x-56 | | 0.5x+0.1(5x)=62.15 | | 4x-20.65=20.1 | | -6f-9f=15 | | 15c+1c+21c= | | 61h=9.3-3.2h | | 7y-10y+6=9 | | x^3-4x+x+6=0 | | 7k-5=19 |

Equations solver categories